Estado de la Salud Mental de un Grupo de Reclusos Pos-Pandemia Covid-19 de la Cárcel y Penitenciaría de Alta y Mediana Seguridad de Palmira, Valle del Cauca (2024)
The purpose of this research was to analyze the mental health of a group of post-Covid19 pandemic inmates from the High and Medium Security Jail and Penitentiary of Palmira, Valle del Cauca, through a qualitative study, phenomenological design, descriptive scope and a nonprobabilistic convenience sample done to five (5) imprisoned people, with whom techniques and instruments were used, such as semi-structured interviews and observation. The data collected was processed and analyzed through a triangulation matrix. The research results expose the complexity of inmates' mental health throughout three distinct phases, like before, during and after the pandemic. In the pre-pandemic stage, a diversity of emotional responses is evident, highlighting the importance of a personalized approach to mental health care, as some of them show resilience and purpose, while others experience negative emotions. During the pandemic, restrictions on visitation and concerns about the spread of Covid-19 intensified stress and anxiety in an already tense prison environment, highlighting the need to address basic needs for safety and belonging; the resilience of inmates during this period is manifested in various strategies. After the pandemic, they experienced post-traumatic growth, finding meaning and strengthening connections with family, spirituality, and mental health.